2021
DOI: 10.5276/jswtm/2021.104
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on Compaction Behavior Of Lateritic Soils Treated with Quarry Dust Based Geopolymer Cement

Abstract: Due to the scarcity of well-graded gravel materials, lateritic soils are widely used for road construction in tropic areas. However, lateritic soils often do not meet the strict requirement for subgrade and need to be improved to be used as construction material. Among several approaches used to enhance the engineering properties of lateritic soils, the use of industrial waste materials, such as fly ash, granulated blast furnace slag, is of particular interest to the construction industry as a potential repla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The decrease can be associated with the addition of geopolymer cements which added more pozzolanic substances into the soil specimen thereby reducing their plasticity. This observed trend is in agreement with Venkaramuthyalu et al (2012), Sadeeq et al (2015), Onyelowe et al (2021). The plasticity index value of the natural kaolin clay of 18.52% was reduced to 7.24% at 20% RHA geopolymer cement content.…”
Section: Consistency Limits Of Geopolymer Cement Treated Kaolin Claysupporting
confidence: 91%
See 1 more Smart Citation
“…The decrease can be associated with the addition of geopolymer cements which added more pozzolanic substances into the soil specimen thereby reducing their plasticity. This observed trend is in agreement with Venkaramuthyalu et al (2012), Sadeeq et al (2015), Onyelowe et al (2021). The plasticity index value of the natural kaolin clay of 18.52% was reduced to 7.24% at 20% RHA geopolymer cement content.…”
Section: Consistency Limits Of Geopolymer Cement Treated Kaolin Claysupporting
confidence: 91%
“…Ohunakin ( 2010) reported that about 80 million cubic metres of fuel wood is being consumed in Nigeria yearly for cooking and other household heating purposes. Onochie et al (2018) reported that the amount of wood waste generated annually in the saw mills is estimated at about 2 million m 3 out of which 20% is sawdust and that Nigerian saw mills skyrocketed from around 500 in 1975 to 1200 in 1981. The current statistics is not well documented but from the trend, it will be in multiple folds in 2022.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are locations in which the limiting conditions were not met. Therefore, mechanical predensification and/or special treatments (mixing with coarse grain materials) [26][27][28][29] of the soils is recommended at these locations using soil compaction machines to reduce the compressibility of the soil before placing the concrete channel's foundation. This settlement problem is an issue of major concern at Chainages 1+000 -1+600 and 2+200 -3+000 as obvious from Table 3.…”
Section: Settlementmentioning
confidence: 99%
“…To enhance more stability of the slopes, it is recommended that steep slopes be stabilized mechanically by ensuring a gentle slope of the embankments [12,29]. In the construction of the engineered embankments, a minimum slope of 1:1 (or gentler) should be considered [5,26] throughout and in cases where this slope cannot be achieved for reasons to be determined by the site engineer, gabion mesh is recommended to compensate the slope for stability. Some of the model plates used for the numerical modelling are presented in Figures 6 and 7.…”
Section: Slope Stabilitymentioning
confidence: 99%